Pengelolaan Sumber Daya Genetik Tanaman Pesisir Kalimantan Tengah: Management of Coastal Plant Genetic Resources in Central Kalimantan - Sudomo, Muhammad Fadhil Amiruddin; Sandi, Jhon Retei Alfri; Yosep, Yosep; Sahay, Marvy Ferdian Agusta; Kriswantara, Glory (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Coastal plant genetic resources (CPGR) are strategic assets for food security, local livelihoods, and climate resilience in Indonesia’s lowland and estuarine landscapes. However, coastal ecosystems in Central Kalimantan are increasingly threatened by land conversion, abrasion, and the rapid diffusion of uniform high-yield varieties. This study analyses the composition, spatial distribution, and management of CPGR in three coastal sub-districts—Teluk Sampit (Kotawaringin Timur), Seruyan Hilir (Seruyan), and Kumai (Kotawaringin Barat)—and formulates strategic directions for their sustainable management. A descriptive–analytical mixed-methods design was applied, combining field observations, soil sampling, semi-structured interviews with farmers, local customary leaders, government agencies, and NGOs, as well as analysis of secondary data and spatial information. Soils across the three sites are dominated by sandy clay loam and loam with strongly to moderately acidic pH (4.4–5.4), high cation exchange capacity, very high exchangeable K, but low Ca–Mg, indicating leached acid coastal soils that favour tolerant crops yet require careful management for intensive agriculture. Coastal plant genetic resources are dominated by mangroves (Rhizophora, Bruguiera, Avicennia), nipah (Nypa fruticans), local coconuts, tidal rice landraces (e.g. Siam Epang and Sekonyer), and emerging horticultural crops such as watermelon and avocado. Each sub-district shows distinct configurations: Teluk Sampit as a mangrove–tidal rice–coconut landscape with a registered geographical indication of Siam Epang; Seruyan Hilir as a nipah–rice–pond mosaic with growing nipah sugar enterprises; and Kumai as a conservation–production mosaic linked to Tanjung Puting National Park and coastal ecotourism. These CPGR underpin household income, employment, and local food systems but face pressures from oil-palm expansion, ageing coconut stands, aquaculture, and infrastructure constraints. Institutional arrangements remain fragmented, with multiple actors but weak formal coordination. Strengthening CPGR management in Central Kalimantan requires integrating in situ conservation with productivity improvement and value addition, recognition and protection of local varieties, and the establishment of an inclusive multi-stakeholder forum and regional action plan to support collaborative governance and long-term coastal resilience.